The Institutional Innovation Through The Integrated Halal System In Management of Hajj Fund Investment in Indonesia - Aminah, Siti; Masruroh, Nikmatul; Wardhana, Firmansyah Shidiq (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
The presence of the COVID-19 disease has had an impact on the pattern of departures for the pilgrimage throughout the world, especially in Indonesia. The lockdown, PSBB, and PPKM policies have had an impact on reducing mass mobilization in the context of preventing COVID 19. The Hajj ban policy has resulted in a longer waiting list for Hajj departures. The longer the waiting list means that the Hajj funds accumulate and must be managed professionally and transparently. Law No. 34 of 2014 mandates the Hajj Fund Management Agency (BPKH) to manage the collected Hajj funds. Previously, 50% of Hajj funds were placed in Islamic banking, it is planned that in 2021 there will be changes. 30% of funds being placed in Islamic banking and 70% being invested in the Islamic investment sector, which is able to provide optimal returns. Therefore, this article was compiled with the aim of providing analysis and proposals for investment innovations that are Sharia-compliant and able to provide benefits for pilgrims who have already made Hajj payments, namely with an integrated halal system. This goal is achieved by using a literature review with Porter's diamond analysis to see the strength of the halal industry in carrying out institutional integration with BPKH. In addition, institutional analysis is also used to explore institutional patterns that should be carried out to achieve optimal management of Hajj funds. This study concludes that in the management of Hajj funds, strong institutions are needed, specifically those that have established Islamic ethics. The principles of trust and honesty are the main foundation for carrying out a halal-integrated system. In the implementation of Hajj fund investment, integration is needed between BPKH, MUI, Ministry of Industry, BPJPH, and companies that are already halal-certified.